2007
DOI: 10.1016/j.ajog.2006.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of retropubic vs transobturator approach to midurethral slings: a systematic review and meta-analysis

Abstract: OBJECTIVE-To systematically review the literature and to quantitatively compare outcomes and complications following retropubic versus transobturator approach to midurethral slings.STUDY DESIGN-We searched PUBMED, OVID, EMBASE, CINAHL, POPLINE, Web of Science, Cochrane Collaboration resources, TRIP, Global Health databases and abstracts from relevant meetings from 1990-2006. We included all studies that compared retropubic and transobturator approaches to midurethral slings and defined outcomes. We used random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(86 citation statements)
references
References 30 publications
(9 reference statements)
4
74
1
6
Order By: Relevance
“…However, they did not assess voiding symptoms, and we believe that the retropubic approach may have a greater chance of de novo urgency. This was confirmed by Sung et al They performed a meta-analysis of TVT and transobturator approach studies and concluded that the transobturator sling operation had a lower risk (odds ratio:0.54) of de novo bladder voiding symptoms than did the TVT procedure [16]. Consistent with the previous study, our data revealed that only 2 (3.6%) patients in the nonobese group and 4 (7.7%) in the obese group complained of de novo urgency, with no significant difference between the groups.…”
Section: Discussionmentioning
confidence: 49%
“…However, they did not assess voiding symptoms, and we believe that the retropubic approach may have a greater chance of de novo urgency. This was confirmed by Sung et al They performed a meta-analysis of TVT and transobturator approach studies and concluded that the transobturator sling operation had a lower risk (odds ratio:0.54) of de novo bladder voiding symptoms than did the TVT procedure [16]. Consistent with the previous study, our data revealed that only 2 (3.6%) patients in the nonobese group and 4 (7.7%) in the obese group complained of de novo urgency, with no significant difference between the groups.…”
Section: Discussionmentioning
confidence: 49%
“…Irritative voiding symptoms are often attributed to the not infrequent development of de novo detrusor overactivity after stress urinary incontinence surgery. This occurs in 18.8% of women receiving a retropubic tape, and 11.4% undergoing transobturator tape placement [3]. The possibility of unrecognized tape perforation or erosion must be considered in women with persistent urinary symptoms, infection or pain after any form of mid-urethral sling procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of complications reported in 1854 patients, bladder perforation was most common, occurring in 3.5% of retropubic sling insertions and in 0.2% of procedures using the transobturator route [3], although incidences as high as 24% have been reported [4]. Although it has been stated that bladder perforation only occurs during the 'outside-in' technique [2,5], there is at least one report to the contrary [6] and it appears likely that complications are under reported [7].…”
Section: Discussionmentioning
confidence: 99%
“…The major advantage of the transobturator approach is the avoidance of the retropubic space, decreasing complications such as bladder and bowel perforation, and major vascular injury. Bladder perforation using the transobturator approach have reported rates as low as 0%, considerably less than those reported for the retropubic procedure [5]. Recent studies report that the transobturator method provides intermediate-term efficacy results that are comparable to the retropubic method with a reduction in major complication risks [8][9][10].…”
Section: Introductionmentioning
confidence: 97%
“…[3,4] Potential complications include bowel injury, bladder injury, major vascular injury, and nerve injury. Bladder perforation in retropubic slings is a common complication with a recent meta-analysis reporting rates of 3.2%, [5] and rates up to 15% have also been reported in at least one multicenter study [6]. Bowel and vascular injuries have also been reported, though less frequently than bladder perforations, but are more serious and have resulted in patient deaths.…”
Section: Introductionmentioning
confidence: 99%